Intelligent Irrigation System Based on ML and IoT - Prof. Shrikant Kokate; Durga Late; Mrunali Padwal; Vivek Khatri; Karthi Dhanasekaran (International Journal of Engineering and Management Research, 2021)
Machine Learning and Internet of Things (IoT) is making advancements in the agricultural sector for better yield quality and effective farming strategies. Due to scarcity of clean water, optimal use of water is required. Less amount of water or excess water can damage the crop. To avoid this, we are designing an Intelligent Irrigation System with the help of IoT and ML Algorithms. ML can help in improving the Irrigation System in such a way that it eradicates crop disease due to excess irrigation, increases yield, optimizes water usage, hence saving clean water. This survey paper aims to help farmers to improve their productivity and quality of crops.